Opportunities for Increasing Russia’s Participation in APEC Development Agenda - Anna Evgenyevna Kuznetsova (Управленческое консультирование)
APEC has a comprehensive development agenda whose importance and scale has been rising steadily over the recent years. Russia has been actively involved into APEC’s work in this field. However, it can be argued that its potential for participation remains largely underutilized. This paper provides examples showing how Russia can go beyond those parts of the APEC development agenda it has been already active at considering both domestic development priorities and its economic interests in Asia-Pacific.